Targeting cell cycle regulators in hematologic malignancies - Aleem, Eiman; Arceci, Robert J. (Frontiers in Cell and Developmental Biology, 2015)
Hematologic malignancies represent the fourth most frequently diagnosed cancer in economically developed countries. In hematologic malignancies normal hematopoiesis is interrupted by uncontrolled growth of a genetically altered stem or progenitor cell (HSPC) that maintains its ability of self-renewal. Cyclin-dependent kinases (CDKs) not only regulate the mammalian cell cycle, but also influence other vital cellular processes, such as stem cell renewal, differentiation, transcription, epigenetic regulation, apoptosis, and DNA repair. Chromosomal translocations, amplification, overexpression and altered CDK activities have been described in different types of human cancer, which have made them attractive targets for pharmacological inhibition. Mouse models deficient for one or more CDKs have significantly contributed to our current understanding of the physiological functions of CDKs, as well as their roles in human cancer. The present review focuses on selected cell cycle kinases with recent emerging key functions in hematopoiesis and in hematopoietic malignancies, such as CDK6 and its role in MLL-rearranged leukemia and acute lymphocytic leukemia, CDK1 and its regulator WEE-1 in acute myeloid leukemia, and cyclin C/CDK8/CDK19 complexes in T-cell acute lymphocytic leukemia. The knowledge gained from gene knockout experiments in mice of these kinases is also summarized. An overview of compounds targeting these kinases, which are currently in clinical development in various solid tumors and hematopoietic malignances, is presented. These include the CDK4/CDK6 inhibitors (palbociclib, LEE011, LY2835219), pan-CDK inhibitors that target CDK1 (dinaciclib, flavopiridol, AT7519, TG02, P276-00, terampeprocol and RGB 286638) as well as the WEE-1 kinase inhibitor, MK-1775. The advantage of combination therapy of cell cycle inhibitors with conventional chemotherapeutic agents used in the treatment of AML, such as cytarabine, is discussed.